2019
DOI: 10.21177/1998-4502-2019-11-2-199-210
|View full text |Cite
|
Sign up to set email alerts
|

An Approach of Mapping Quarries in Vietnam Using Low-Cost Unmanned Aerial Vehicles

Abstract: Журнал входит в Перечень изданий, рекомендованных Высшей аттестационной комиссией (ВАК) Журнал включен в международную реферативную базу данных и систему цитирования Scopus Адрес редакции, учредителя, издателя: 362021, РСО-Алания, г. Владикавказ, ул. Николаева, 44, Северо-Кавказский горнометаллургический институт (государственный технологический университет), редакция журнала «Устойчивое развитие горных территорий».

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
7
0
2
Order By: Relevance
“…Also, the accuracy of DSM increases asymptotically with an increasing number of Submission date: 06-03-2020 | Review date: 22-09-2020 GCPs until a certain density of GCPs is reached (Gindraux et al, 2017). It is shown that the cm-level accuracy can be achieved with no less than five GCPs in most terrain conditions (Lee & Choi, 2015;Nguyen Quoc Long et al, 2019;Siebert & Teizer, 2014) and this requires even more than ten GCPs with complex terrain such as that in open-pit mining sites(Dieu Tien Bui et al, 2017). However, GCP acquisition is impeded by site access difficulties or hazardous circumstances (Ekaso et al, 2020), so a large number of GCPs could reduce the mine surveying efficiency.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, the accuracy of DSM increases asymptotically with an increasing number of Submission date: 06-03-2020 | Review date: 22-09-2020 GCPs until a certain density of GCPs is reached (Gindraux et al, 2017). It is shown that the cm-level accuracy can be achieved with no less than five GCPs in most terrain conditions (Lee & Choi, 2015;Nguyen Quoc Long et al, 2019;Siebert & Teizer, 2014) and this requires even more than ten GCPs with complex terrain such as that in open-pit mining sites(Dieu Tien Bui et al, 2017). However, GCP acquisition is impeded by site access difficulties or hazardous circumstances (Ekaso et al, 2020), so a large number of GCPs could reduce the mine surveying efficiency.…”
Section: Introductionmentioning
confidence: 98%
“…Mine surveying is one of the most critical tasks in openpit mines (Nguyen Quoc Long et al, 2019). Surveying engineering, topological survey, and volumetric computation are undertaken on a daily basis (Le Van Canh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…With the advanced development of unmanned aerial vehicle (UAV) technology in recent years, UAV has been applied in different mining activities including pit and dump manage-ment (Padró et al, 2019), stockpile computation (Le, 2020;Raeva et al, 2016), blast-induced ground vibration (X.-N. Bui et al, 2020), and 3D mapping open-pit mines (D. T. Bui et al, 2017; N. Q. Long et al, 2019;Nghia, 2020). In the field of mining environment management, it is noted that UAV carrying modular gas sensors is an effective monitoring system of air quality (Rohi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Application of UAV data in mapping has been studied and used by many scientists. With the advanced development of UAV technology in recent years, UAV has been applied in different mining activities including blast-induced ground vibration (Bui et al, 2020), mapping open-pit mines (Long et al, 2019;Bui et al, 2017;Nghia, 2020), stockpile computation (Canh, 2020), and pollution monitoring (Bui et al, 2019).…”
Section: Introductionmentioning
confidence: 99%